Aquifer layer in Muara Batu and Dewantara Sub-district based on resistivity cross-sectional model - SYAFRIZAL IDRIS; MULIANI MULIANI; NANDA NOVITA (Universitas Syiah Kuala, 2023)
This study aims to determine the depth of the aquifer layer in the Muara Batu and Dewantara sub-district as a source of groundwater that can be used continuously. The identification of this aquifer layer is based on the results of the resistivity values of subsurface rocks measured using the electrical resistivity method of the Schlumberger array. Data acquisition was carried out on 3 lines (MB1, MB3, and MB4) with a length of 330 m each. The variations in the resistivity values of the rocks obtained were modeled in the form of a 2D cross-section using the Res2DInv software, thus providing an overview of the subsurface for groundwater exploitation. The cross-sectional model obtained shows that the shallow aquifer layer is at a depth of 20-52 m (2-12 Ωm) on the MB1 and a depth of 60 m on MB3 and MB4. The low resistivity value 12 Ωm on the MB1 indicates that the subsurface is generally composed of water-saturated rock layers.